Dynamic response of multibody systems with multiple clearance joints - Flores, Paulo (2011)
A general methodology for the dynamic modeling and analysis of planar multibody systems with multiple clearance joints is presented. The inter-connecting body components that constitute a real joint are modeled as colliding bodies, which dynamic behaviors are influenced by geometric, physical and mechanical properties of the contacting surfaces. A continuous contact force model, based on the elastic Hertz theory, together with a dissipative term, is used to evaluate the intra-joint contact forces. The incorporation of the friction, based on the classical Coulomb’s friction law, is also included. The suitable contact force models are embedded into the dynamic equations of motion for the multibody system. A simple mechanical system with multiple clearance joints is used to demonstrate the accuracy and efficiency of the presented approach and to discuss the main assumptions and procedures adopted. The effects of single versus multiple clearance joints are discussed.